Case Study: Exploring Learners’ Emotional States in Practicing the 5R’s Self Reflective Strategies on Their Reading Activities - Astuty, Diah; Farih, Abdullah (Tell : Teaching of English Language and Literature Journal, 2021)
This study presented the exploration on learners' emotional states while they're practicing the 5R's self reflective strategies. The 5Rs consists of reporting stages, responding stages, relating stages, reasoning stages and reconstructing stages. Participants of this study are 20 students of a local university at East Java Province. The method of this study is institutional case study. The data in this study are learners' learning logs and online interview via zoom.